Parental Upbringing and Its Relationship to Anxiety and Aggressive Behavior in A Sample of Students of The Intermediate Stage in Al- Makhwah Governorate. - Al-Omari, Hussein Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the relationship between parental upbringing, anxiety and aggressive behavior in a sample of students in the Intermediate stage in Al- Makhwah Governorate. To achieve the study objectives, the researcher used the descriptive approach with its correlation form. The study relied on three tools: the parental upbringing scale (By Atwi, 2006) Anxiety (By: Al- Qarni, 1435 H), and the measure of aggressive behavior (By: Zahrani, 1436 H), The study population was composed from Intermediate school students in Al- Mahwah Governorate which was (3259) student, while the sample was randomly selected. The number of students was 327. The study found that: the most preferred method of parenting in (father’s form) were the authoritarian pattern, followed by the pattern of neglect and finally the democratic pattern, while the most favored in (mother’s form) were the democratic pattern followed by the authoritarian pattern, and finally the pattern of neglect. Also, the results showed that there was a statistically significant correlative relationship at (α 0.05)between the dimensions of the parenting scale and the anxiety scale except after the democratic pattern in (father’s form), also there was a statistically significant relation at (α 0.05)between the dominant pattern and all areas of the anxiety scale except the mental side (mother’s form), There was a statistically significant relationship at (α 0.05)between the pattern of neglect in (father and mother form) and the domains of the anxiety scale except Cognitive and mental side, The results showed that there was a statistically significant correlation at (α 0.05)between the absolute pattern of the parenting method and the aggressive behavior measure (father / mother). The study recommended focusing on the use of the father and mother for guidance and guidance in dealing with children, using the pattern of democratic treatment and engaging in meaningful discussions with them about their concerns. And all related to their daily lives to find a strong moral and intellectual link between them and their parents to spare them mental disorders related to anxiety and aggressive behavior, as well as activate the role of guidance and guidance programs for parents and their children in schools, and try to discuss their problems through them.